ANALISIS PENGENDALIAN KUALITAS DALAM UPAYA MENEKAN JUMLAH KERUSAKAN PRODUK AKHIR PADA PT.BOEHRINGER INGELHEIM INDONESIA - Yumaidila, Mida; Silaningsih, Endang (JURNAL VISIONIDA, 2016)
PT. Boehringer Ingelheim, located at Jalan Lawang Gintung 89, Sub-Bogor Sukasari, was founded in 1885, Germany. PT Boehringer Ingelheim Indonesia Groups is one of the worldâs 20 leading pharmaceutical in manufacturing and producting medicines for humans phamaceutical and animal heatlh. The type product produced by PT. Boehringer Ingelheim Indonesia are solid medicines (tablet, the film coating, sugar coating), semisolid medicines (suppository, emulgel & cream), and liquid medicines (syrup and suspension). To maintain consumer belief PT. Boehringer has controlled both raw quality and packaging materials, the production process and the finishing product. PT. Boehringer Ingelheim Indonesia has established the standard damage of product tolerance of 5%âs total production. However, the reality on the field shows that the level of the most widely produced products and exceeded the control limit is Bisolvon Ex 60 ml, 60 ml and Kids Bisolvon Bisolvon Ped 60 ml. Analysis of the quality control is done by using statistical tools those are check sheet, control chart p, pareto diagrams and fishbone. The research result indicates that PT. Boehringer Ingelheim Indonesia needs to improve to hold down and reduce the amount of damage that occurred during the production process.Keywords: Quality Control, Check Sheet, Control Chart P, Pareto Diagram, dan Fishbone Chart.